STUDENT’S MOTOR PERFORMANCE FITNESS ANALYSIS AT ELEMENTARY SCHOOL TEACHER STUDY PROGRAM UNIVERSITY OF MATARAM - Prayogi Dwina Angga; Hikmah Ramdhani Putri (PROGRES PENDIDIKAN, 2023)
Physical fitness and physical activity are the main modalities for physical and mental health, but the level of physical activity and physical fitness decreases in adolescents, especially college students. This study examines physical performance which is a component of physical fitness in college students. Research using a survey with a descriptive approach. 30 students of the Elementary School Teacher Education Study Program (PGSD) of the Faculty of Teacher Training and Education (FKIP) at the University of Mataram consisting of 15 boys and 15 girls with an average age of 18.93 years were involved in this research. The data collection technique used a performance test, namely (1) a standing long jump test (broad jump) to measure the explosive power of the leg muscles; (2) an Agility Shuttle 10 meters (4 x 10 meters) which aim to measure agility and running speed; (3) 20 Meter Dash which aims to know the speed. Data analysis using descriptive statistics. The results showed that the basic locomotor skills of PGSD students were included in the low category. It is necessary to identify the factors that influence the low interest in physical activity of students and formulate appropriate strategies to increase physical activity and physical fitness of PGSD students.